Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1016/j.iree.2018.01.003
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the flipped classroom in a principles of microeconomics course: evidence from a quasi-experiment with two flipped classroom designs

Abstract: This study uses a quasi-experimental, non-equivalent group design to analyze the outcomes in terms of students' learning and satisfaction of the redesign of a first-year, principles of microeconomics course from a lecture-based course using active learning techniques in 2013 to a partial flipped classroom in 2014 and a full flipped classroom in 2015. Students perceived a higher degree of achievement of the learning goals in both flipped courses compared to the non-flipped active learning course. Moreover, part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
36
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 25 publications
(26 reference statements)
5
36
0
2
Order By: Relevance
“…The satisfaction and positive feelings towards this teaching methodology and against LB have been demonstrated in several research studies [19, 3537], but there are also studies in which student satisfaction does not differ between both teaching strategies [3839].…”
Section: Discussionmentioning
confidence: 99%
“…The satisfaction and positive feelings towards this teaching methodology and against LB have been demonstrated in several research studies [19, 3537], but there are also studies in which student satisfaction does not differ between both teaching strategies [3839].…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5]. Both learner-centered and learner-driven learning approaches are based on constructivist learning theory, which was proposed by Jean Piaget for whom learning was an active process where learners must actively construct their knowledge through prior knowledge and experiences [3,6].…”
Section: Introductionmentioning
confidence: 99%
“…In the UK higher education system, a student who gets an overall grade below 40% fails the course. Following, Lombardini et al [8], I employed a binary logit regression model. In this model, the dependent variable was coded as 1 if the student's overall grade was below 40% and 0 otherwise.…”
Section: Data Sourcesmentioning
confidence: 99%
“…Studies have revealed that a significant proportion of undergraduate students only acquire conceptual knowledge of the subject in a traditional classroom format. They are not able to adequately develop critical thinking, data analysis and reasoning skills, which are thought to be at the core of the curriculum [8]. Employers also reveal that many Business school graduates are not good at applying economic and finance principles to real world issues [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation